Current research status and trends in the bioactivity of postbiotics - Chen, Xueling; Yuan, Can; He, Jiang; Li, Wanwu; Liao, Cheng (Frontiers in Food Science and Technology, 2025)
Postbiotics have similar bioactivity to probiotics and are safer and more stable. The results indicate that postbiotics exert their effects through direct (antibacterial, antioxidant, immune regulatory) and indirect (regulating microbial homeostasis and metabolic pathways) mechanisms. In the field of animals, postbiotics can enhance the disease resistance of aquatic animals, improve the intestinal health and meat quality of broiler chickens, and promote nutrient absorption in ruminant animals. In the field of humans, postbiotics exhibit potential for anti-allergy, prevention of respiratory or digestive tract infections, adjuvant therapy for anti-cancer, and improvement of liver cirrhosis. Meanwhile, postbiotics have been applied in the research and development of medical preparations and functional foods, but the mechanism of action still needs to be further explored. Compared to probiotics, postbiotics do not require live bacteria to produce health benefits and have advantages such as high safety, easy storage, and convenient production. In the future, postbiotics have broad prospects in the fields of functional foods with unique flavors and nutritional health benefits, and disease prevention and control.